HIGH STRAIN-RATE COMPRESSIVE TESTING OF FILLING MATERIALS FOR INTER-PENETRATING PHASE COMPOSITES - Tomáš Doktor; Tomáš Fíla; Petr Zlámal; Daniel Kytýř; Ondřej Jiroušek (Acta Polytechnica CTU Proceedings)
In this study behavior of the selected types of filling material for the inter-penetrating phase composites was tested in compressive loading mode at low and high strain-rates. Three types of the filling material were tested, (i) ordnance gelatin, (ii) low expansion polyurethane foam, and (iii) polyurethane putty. To evaluate their impact energy absorption bulk samples of the selected materials were tested in compression loading mode at strain-rates 1000 s−1 to 4000 s−1. The high strain-rate compressive loading was provided by Split Hopkinson Pressure Bar (SHPB) which was equipped with PMMA bars to enable testing of cellular materials with low mechanical impedance. Based on the comparative measurement response to compression at both low and high strain-rates was analysed. The results show a significant strain-rate sensitivity of the ordnance gelatin and of the polyurethane putty, while strain-rate effect in the polyurethane foam was not observed.